Analisis User Interface pada Media Pembelajaran Bahasa Inggris Berbasis Game Visual Novel - Deli Deli (Politeknik Negeri Batam, 2021)
Heuristic evaluation in applicating of system evaluation is considered capable of being used in analyzing and testing the level of ease in operating visual-based English novel as learning media. The evaluation does not limit the assessment and measurement of the level of usability of the system by involving end users in the work and testing process. Therefore, heuristic evaluation is needed to determine how high the usability level of English learning media based on visual novels in the use of learning media. The research sample was aimed at the first semester of Information System department’s students to provide an assessment of user interface of the learning media using probability sampling, proportionate stratified random sampling as the focus of the sampling technique that will fill out the questionnaire. The data in the study will be analyzed using a mix of qualitative and quantitative descriptive analysis methods. Based on the results of the study, it is stated that the visual-based English novel learning media interface layout design will be able to meet the criteria for heuristic evaluation and has good usability criteria and is easy to operate by users.